Environmentally benign catalytic process for esterification of renewable levulinic acid to various alkyl levulinates biodiesel - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2015)
This study explores, the use of modified zeolite (Micro/Meso-HZ-5) obtained by desilication post-treatment as heterogeneous catalyst for esterification of biomass derived renewable levulinic acid (LA) with different alkyl alcohols such as methanol, ethanol, n-butanol, and n-octanol aiming to produce corresponding alkyl levulinate. This method of production of alkyl levulinates would be sustainable process, as it can be used as novel miscible diesel biofuels preventing global warming by decreasing atmospheric CO2. The LA conversion obtained over Micro/Meso-HZ-5 was higher than H-ZSM-5, which is due to the combined effect of increase in Bronsted acid sites, total acidity, and other properties such as BET surface area and the generation of mesoporosity. The maximum LA conversion of 91, 95, 96, and 98% with 100% selectivity toward alkyl levulinate was obtained, when LA was being esterified over Micro/Meso-HZ-5 with methanol, ethanol, n-butanol, and n-octanol, respectively, at optimal process parameters. Micro/Meso-HZ-5 catalyst was found to be reusable for six cycles. Furthermore, pseudo homogeneous (P-H) kinetic model of the esterification of LA with the studied four alcohols were established with R-2>0.99, using the experimental data. A P-H kinetic model implies that, the esterification reaction follows second order reversible kinetics. (c) 2014 American Institute of Chemical Engineers Environ Prog, 34: 795-801, 2015
Keywords: biofuels; Esterification; kinetic model; levulinic acid; meso-HZ-5; micro